2021
DOI: 10.3892/ijo.2021.5203
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic role of abnormal spindle‑like microcephaly‑associated protein in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) is a common malignant cancer worldwide. It is urgent to explore its underlying molecular mechanism and identify novel diagnostic biomarkers. Abnormal spindle-like microcephaly (ASPM) has recently received considerable attention due to its function in tumor progression. However, its role in LUAD is unclear. The present study aimed to explore the clinical role of ASPM in LUAD. Seven pairs of LUAD and adjacent normal tissues were collected to identify potential LUAD biomarkers using tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Deciphering signaling pathway networks is important for understanding the molecular mechanisms of IMPA function. As previously reported, KIF14 promotes the proliferation by regulating the phosphorylation of AKT, 18 and ASPM regulates lung adenocarcinoma cell metastasis by promoting epithelial‐mesenchymal transition (EMT) through the PI3K/Akt signaling pathway 19 . FAM83D is associated with EMT process 20 and regulates cancer cell proliferation and migration through Akt/mTOR pathway 21 .…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Deciphering signaling pathway networks is important for understanding the molecular mechanisms of IMPA function. As previously reported, KIF14 promotes the proliferation by regulating the phosphorylation of AKT, 18 and ASPM regulates lung adenocarcinoma cell metastasis by promoting epithelial‐mesenchymal transition (EMT) through the PI3K/Akt signaling pathway 19 . FAM83D is associated with EMT process 20 and regulates cancer cell proliferation and migration through Akt/mTOR pathway 21 .…”
Section: Resultsmentioning
confidence: 76%
“…As previously reported, KIF14 promotes the proliferation by regulating the phosphorylation of AKT, 18 and ASPM regulates lung adenocarcinoma cell metastasis by promoting epithelial‐mesenchymal transition (EMT) through the PI3K/Akt signaling pathway. 19 FAM83D is associated with EMT process 20 and regulates cancer cell proliferation and migration through Akt/mTOR pathway. 21 Moreover, KIF20B mediates colorectal cancer cell migration and invasion though promoting EMT process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, ASPM has been proved to participate in the cancers progression through diverse mechanisms. Wang J et al suggested that ASPM served an crucial oncogenic part in regulating LUAD cell migration by facilitating epithelial‐mesenchymal transition via the PI3K/AKT pathway, 10 and Yuan Y J et al clarified that ASPM contributed to the development of LSCC by mediating CDK4 11 . However, whether and how ASPM regulates LIHC progression remain elusive.…”
Section: Introductionmentioning
confidence: 99%